A poly(thymine)-templated fluorescent copper nanoparticle hydrogel-based visual and portable strategy for an organophosphorus pesticide assay. Issue 7 (28th February 2019) - Chen, Jihua; Han, Ting; Feng, Xiuyun; Wang, Baojuan; Wang, Guangfeng
Abstract : Since fluorescence assays with high sensitivity for organophosphorus pesticides (OPs) are urgently required to protect the ecosystem and prevent disease, an environmentally friendly and label-free fluorescent probe is desirable. Abstract : Since fluorescence assays with high sensitivity for organophosphorus pesticides (OPs) are urgently required to protect the ecosystem and prevent disease, an environmentally friendly and label-free fluorescent probe is desirable. Herein, a poly-thymine30 DNA-templated copper nanoparticle (poly T30-Cu NPs) hydrogel fluorescent probe was explored for the construction of an OPs sensing platform via tyrosinase (TYR) enzyme-controlled quenching. Initially, TYR can efficiently quench the fluorescence of poly T30-Cu NPs; however, when OPs are mixed with a certain amount of TYR, the fluorescence of poly T30-Cu NPs can be recovered. Based on this phenomenon, we designed a functionalized hydrogel based on poly T30-Cu NPs for portable and visible detection of OPs with high sensitivity and selectivity. This proposed fluorescent platform was demonstrated to enable rapid detection of OPs (paraoxon as the model analyte) and provide excellent sensitivity with a detection limit of 3.33 × 10 −5 ng μL −1 and a linear range of 1.0 × 10 −4 –1.0 ng μL −1 . The fluorescent probe does not require a sophisticated synthesis and labeling process; in addition, it is environmentally friendly because of the presence of a biotemplate of DNA and biocompatible copper. Moreover, the functional hydrogel combines the features of portability, visualization, fast signal response and environmental anti-interference that make the proposed strategy more feasible in complex practical detection.